Structural divergence of plant TCTPs - Gutiérrez-Galeano, Diego F.; Toscano-Morales, Roberto; Calderón-Pérez, Berenice; Xoconostle-Cázares, Beatriz; Ruiz-Medrano, Roberto (Frontiers in Plant Science, 2014)
The Translationally Controlled Tumor Protein (TCTP) is a highly conserved protein at the level of sequence, considered to play an essential role in the regulation of growth and development in eukaryotes. However, this function has been inferred from studies in a few model systems, such as mice and mammalian cell lines, Drosophila and Arabidopsis. Thus, the knowledge regarding this protein is far from complete. In the present study bioinformatic analysis showed the presence of one or more TCTP genes per genome in plants with highly conserved signatures and subtle variations at the level of primary structure but with more noticeable differences at the level of predicted three-dimensional structures. These structures show differences in the “pocket” region close to the center of the protein and in its flexible loop domain. In fact, all predictive TCTP structures can be divided into two groups: 1) AtTCTP1-like and 2) CmTCTP-like, based on the predicted structures of an Arabidopsis TCTP and a Cucurbita maxima TCTP; according to this classification we propose that their probable function in plants may be inferred in principle. Thus different TCTP genes in a single organism may have different functions; additionally, in those species harboring a single TCTP gene this could carry multiple functions. On the other hand, in silico analysis of AtTCTP1-like and CmTCTP-like promoters suggest that these share common motifs but with different abundance, which may underscore differences in their gene expression patterns. Finally, the absence of TCTP genes in most chlorophytes with the exception of Coccomyxa subellipsoidea, indicates that other proteins perform the roles played by TCTP or the pathways regulated by TCTP occur through alternative routes. These findings provide insight into the evolution of this gene family in plants.